Strategi Pengembangan Agribisnis Puring di Desa Petiga, Kecamatan Marga, Kabupaten Tabanan - IGA. WIDARI UPADANI; DWI PUTRA DARMAWAN; IM. NARKA TENAYA (JURNAL MANAJEMEN AGRIBISNIS, 2013)
Croton (Codiaeum variegatum) has become a valuable ornamental plant because of the beauty of its colorful unique features of leaves that is worth to collect. Farmers from Petiga Village have been trying to develop croton as the object of business. A huge prospect of ornamental plant as the development in Bali emerging, bring hopes for the future of croton agribusiness. Yet, there are still many aspects that have to be taken into consideration in order to bring this business prospective especially to Petiga Village farmers. This research was conducted at Petiga Village, Marga District, Tabanan Regency with the aim at: (1) identifying internal factors (strengths and weaknesses) and external factors (opportunities and threats). (2) determining the position of the business, (3) formulating strategies that are relevant to be applied. Respondents of this research were determined on purpose, including the farmer, head of farmer groups, village agriculture field supervisor, and the head of Agriculture Departement from Tabanan Regency. Data analysis methods used were: (1) Analysis of IFE matrix, (2) Analysis of EFE matrix, (3) Analysis of the IE matrix, (4) SWOT Analysis, and (5) Analysis of AHP. The results of the study showed that the major constraint of the progress development of croton agribusiness at Petiga Village was that most of the farmer lack of information regarding the market and the price of the product. Only a small group of farmers had an access to the direct market of croton. The study also identify two major internal strengths : good quality product (croton) and the possibility of developing new variety of croton with better prices. While the external threats come from other kind of ornament plant and croton from other regions (East Java). SWOT analysis formulates four alternative strategies : improving the quantity and quality of the product, improving marketing and promotion, improving management and entrepreneurship skill of the farmer and improving coordination and consolidation among farmers. Analysist of Hierarchy Process found that improving management and entrepreneurship of the farmers had a higher priority above other alternative strategies. This strategy could be perform by delivering practical training and close supervision on the site to give them a direct benefit.